Electrochemical Formation of Li-M-(Mʹ)-Si Phases Using Multivalent Electrolyte Salt Additives. Issue 3 (1st March 2023) - Uppuluri, Ritesh; Lapidus, Saul H.; Zhang, Yunya; Vaughey, John T.; Dogan, Fulya; Key, Baris
Abstract : Lithium-rich silicides (Li15 Si4 ), formed during the electrochemical lithiation of silicon, show high reactivity with electrolyte components that contribute to capacity decay, formal lithium loss, and low coulombic efficiency. Recently, the reactivity of lithium silicides was found to be suppressed by substituting a multivalent cation (i.e. Mg, Ca) for lithium that results in the room temperature formation of a ternary Li-M-Si phase. In this study, we explored a range of multivalent electrolyte salt additives (M = Ni, Cu, La, Ce, Sr, Ba, and Ca-Mg mixed salt) in a lithium-ion cell configuration and identified a room temperature electrochemical route to the formation of new ternary and quaternary lithium silicides. Using this method, both nickel and copper salts were found to plate onto the silicon electrode surface upon lithiation. Based on refined synchrotron XRD data, multivalent cations with an ionic radius similar to Na (∼1.03 Å) or smaller can be inserted electrochemically into a formally cation-deficient Li15 Si4 host lattice to form new ternary (or quartenary) phases. The electrochemical synthesis of a new quaternary Li-M-M'-Si phase represents a facile route to preparing and scaling materials isostructural to the Heusler phase and electron-precise Li14 MgSi4 phase that results in enhanced cycling and calendar life performance.